Demonstrative Study of the Effectiveness of Low Cost Gully Rehabilitation Measures: The Case of Bonke District SNNPR, Ethiopia (Global Journal of Science Frontier Research, 2020)
Gully erosion is the major environmental problem threatening the huge areas of agricultural land in Southern Ethiopia, particularly the Gamo Gofa zone of Bonke district. The present study is aimed at evaluating and demonstrating low-cost gully treatment methods for gully rehabilitation in Bonke district SNNPR, Ethiopia. Three treatments namely, Brushwood check dam+ trench+ head apron, brushwood with stone check dam+ trench+ head apron, and Stone check dam+ trench+ head apron) established in 6 gullies. Building the check-dams, Jatropha, elephant grass, and banana were planted. Data such as sediment deposition and biomass production were collected to investigate their effectiveness in reducing soil erosion and biomass production. Also, the costs for establishing the rehabilitation measures were collected. The Considerable differences among the tested trials in reducing soil erosion and biomass production was not observed. However, the rehabilitation measures maintained the restoration of grass and shrub species as well as the improvement of soil fertility. It is detected that the cost of establishing brushwood check damis considerably low compared to the other tested methods.
Keywords: check-dam; grasses biomass; gully rehabilitation; low cost